KHGT Muhammadiyah: Bukti Nyata Islam Sejalan dengan Ilmu Pengetahuan Modern - Nadiva Gita Syamsiyah; Cantika Adelia Fahmasari; Ahmad Fu’ad Abdul Baqi (Pascasarjana IAI Al-Khairat Pamekasan, 2025)
Differences in determining the beginning of lunar months particularly Ramadan, Shawwal, and Dhu al-Hijjah remain a recurring phenomenon that affects Muslim communal cohesion and the certainty of religious and social scheduling. Muhammadiyah proposes the Single Global Hijri Calendar or Kalender Hijriah Global Tunggal (KHGT) as an effort to unify the Hijri calendar based on the one day one date principle so that the same civil day corresponds to a single Hijri date worldwide. This study aims to explain the definition and objectives of KHGT, examine its scientific foundations particularly hisab hakiki or astronomical calculation and crescent visibility approaches along with their linkage to Islamic legal proofs, demonstrate how KHGT reflects harmony between Islam and modern science in determining worship times, and identify challenges to its regional and global implementation. The research employs a qualitative library research design using documentation and content analysis of Indonesian journal literature from the last five years as well as relevant KHGT-related documents. The findings show that KHGT emphasizes calendar certainty and long-term predictability through measurable and replicable modern astronomical computation, while its shar‘i legitimacy is framed through interpretive readings that prioritize ensuring the verified entry of a new lunar month. KHGT thus demonstrates a complementary relationship in which Islamic law provides normative aims and science functions as a verification instrument. The main challenges lie in consensus building, including differing criteria among organizations and states, acceptance of regional standards such as MABIMS or Neo MABIMS, and the need for international agreement on matlak and a global Hijri date line.